Metode Kooperatif Tipe Teams Games Tournaments Dalam Meningkatkan Hasil Belajar Siswa - Abriyanto, Heru; Megawati, Megawati; Retnowati, Kiki (Journal of Innovation in Teaching and Instructional Media, 2022)
This research aims to investigate the effectiveness of the Teams Games Tournaments (TGT) type cooperative method in improving student learning outcomes. This research method involves the participation of students from various groups in academic games and tournaments to motivate cooperation and healthy competition. The research results showed a significant increase in the learning achievement of students who applied the TGT method compared to the control group. The uniqueness of this research lies in the implementation of the TGT method in an educational context and a deeper understanding of how collaboration and positive competition can help improve learning outcomes. The main contribution of this research is to provide empirical evidence about the benefits of the TGT method in improving student learning outcomes in various disciplines. This research also provides valuable insights for educational practitioners in the development of teaching methods that promote collaboration and student motivation in achieving better academic achievement.